1921 Minn. Laws 742 - (:unkn) unknown (My University, 1921)
An Act to Provide for the Incorporation, Organization and Government of Cities of Ten Thousand (10,000) Inhabitants or Less, (Cities of the Fourth Class), ch. 462, § 41, pt. 37: To regulate and prevent the storage of gunpowder, dry pitch, resin, coal oil, benzene, naptha, gasoline, turpentine, hemp, cotton, nitroglycerine or any products thereof, and other combustible or explosive materials within the city, and the use thereof[.]
Keywords: GUNPOWDER - STORAGE